Using an Integration Model in researching destination loyalty of international tourists: Empirical evidence from Danang City, Vietnam - Le Duc Toan (African Journal of Hospitality, Tourism and Leisure, 2020)
This study’s aim was to propose an integrated model to examine the antecedents and the direct and indirect relationship between the antecedents that affect international tourists’ destination loyalty in Danang, Vietnam. Based on the prior studies, this paper added safety and security constructs in the research model, and the study’s findings reveal that safety and security, image, perceived value and satisfaction are likely to be the antecedents of international tourists’ destination loyalty in Danang destination. This study could contribute in enriching the tourism and hospitality literature by examining factors that will lead to international tourists’ destination loyalty, using data collected from Danang tourism destination. The study also proposes some likely usable recommendations for tourism marketers and managers.